IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN IPAS SD NEGERI KROYO 4 - Bella Amani Fatekhah, Tiara Putri Pranoto, Irfan Khairuddin Al mawardi, Septyana Candra Puspita, Vit (Elementary School and Education Journal, 2025)
This research aims to describe the implementation of the independent curriculum in science and science learning at SD Negeri Kroyo 4. The subject of this research is the class IV homeroom teacher. This research uses a descriptive qualitative approach using literature study methods, documentation and interviews. The research results show that teachers have implemented various learning strategies such as discussion, direct practice, and the use of relevant learning media that has integrated technology in it. Learning is adjusted to characteristics and abilities based on diagnostic assessments to determine student learning styles. Even though there are still challenges such as differences in character and incompatibility of material, the independent curriculum is considered to be able to increase the effectiveness of learning and encourage student involvement in the learning process, but teachers and school stakeholders continue to make efforts to implement it.